PROXIMAL: a method for Prediction of Xenobiotic Metabolism. - Yousofshahi, Mona.; Manteiga, Sara.; Wu, Charmian.; Lee, Kyongbum.; Hassoun, Soha. (2016)
Background: Contamination of the environment with bioactive chemicals has emerged as a potential public health risk. These substances that may cause distress or disease in humans can be found in air, water and food supplies. An open question is whether these chemicals transform into potentially more active or toxic derivatives via xenobiotic metabolizing enzymes expressed in the body. We present a new prediction tool, which we call PROXIMAL (Prediction of Xenobiotic Metabolism) for identifying possible transformation products of xenobiotic chemicals in the liver. Using reaction data from DrugBank and KEGG, PROXIMAL builds look-up tables that catalog the sites and types of structural modifications performed by Phase I and Phase II enzymes. Given a compound of interest, PROXIMAL searches for substructures that match the sites cataloged in the look-up tables, applies the corresponding modifications to generate a panel of possible transformation products, and ranks the products based on the activity and abundance of the enzymes involved.; Keywords: Xenobiotic metabolism, Environmental chemical, Molecular substructure, Phase I and Phase II enzymes.; Springer Open.